Obstructive Jaundice Due to Hydatid Cyst: Case Report - Cuiabano Arruda Borges, Beatriz; Kober Manzoni, Juan; Galdino de Oliveira Borges, Luccas; Alberto Tomatis Loth, Carlos (Brazilian Journal of Case Reports, 2024)
Hydatid cyst is a parasitic disease caused by Echinococcus granulosus, common in endemic regions and characterized by the development of cysts in the liver or lungs. This report describes the case of a 25-year-old patient from a rural area in southern Brazil who presented with obstructive jaundice caused by a large hepatic hydatid cyst. The diagnosis was confirmed through imaging exams (MR cholangiography) and serology. Treatment consisted of albendazole administration followed by successful surgical excision of the cyst, with no complications. The patient showed positive progress and was discharged on the tenth postoperative day. This case underscores the importance of early diagnosis and proper management of hydatidosis, as well as the need for control strategies in endemic areas.